Association between residential exposure to petrochemical industrial complexes and pancreatic cancer: a systematic review and meta-analysis. Issue 1 (2nd January 2023) - Boonhat, Hathaichon; Lin, Ro-Ting; Lin, Jaw-Town
ABSTRACT: Increased in the global demand–expansion of the petrochemical industry is a possible environmental risk factor pancreatic cancer among residents living close to petrochemical complexes. This meta-analysis aimed to estimate the pooled risk of pancreatic cancer among residents living near petrochemical industrial complexes. We systematically searched and reviewed published studies in six databases based on the inclusion criteria derived from the population, exposure, comparator, and outcomes framework (population: general population; exposure: residence near petrochemical industrial complexes/living in cities with petrochemical industrial complexes; comparators: residents living farther away from petrochemical industrial complexes/living in cities without petrochemical industrial complexes; outcome: pancreatic cancer). We identified seven studies, covering 1, 605, 568 residents. Pooled analysis showed a significantly higher risk of pancreatic cancer among residents living near petrochemical industrial complexes (relative risk [RR] = 1.31, 95% confidence interval [CI] = 1.21–1.42) than those living farther away from petrochemical industrial complexes. Such effect was higher in female residents (RR = 1.34, 95% CI = 1.18–1.53) than in male residents (RR = 1.26, 95% CI = 1.12–1.41). This study suggests that exposure to petrochemical industry-related activities should be recognized as a risk factor for pancreatic cancer among residents living near petrochemical industrial complexes.